Temporomandibular‐disorder‐related pain as a predictor of severe headaches. Issue 3 (7th May 2021) - Ashraf, Javed; Närhi, Matti; Suominen, Anna Liisa; Zaproudina, Nina; Saxlin, Tuomas
Abstract: Objective: The current study aimed to investigate the association of temporomandibular disorders (TMD)‐related pain with the presence of migraine or tension‐type headaches (TTH) over a follow‐up period of 11 years. Methods: Data sets from Finnish national health surveys, the Health 2000 Survey (baseline), and the Health 2011 Survey (follow‐up) were utilized. Study participants are undergoing clinical TMD examination at baseline and answering questions related to the presence of migraine and TTH at follow‐up were included in the study (n = 530). For analyses, the study sample was divided into two data sets: One with those excluded suffering from migraine at baseline (Data set I, n = 345), and the other excluding those having TTH at baseline (Data set II, n = 464). Results: Based on logistic regression modelling, no consistent association between TMD‐related pain and the presence of migraine was observed, although jTMD associated with elevated estimates for migraine. However, participants with muscle‐related TMD pain (mTMD) at baseline had markedly higher odds for having TTH at follow‐up than participants without mTMD at baseline (OR 2.1, 95% CI 1.2‐3.8). Joint‐related TMD pain (jTMD) at baseline was inversely associated with the presence of TTH at follow‐up (OR 0.4, 95% CI 0.1‐1.3). Conclusion: Contrasting patterns of the associations of TMD‐related pain with different severe headaches point towards a more thorough and systematic research approach are needed to understand the mechanisms behind these associations.